Integrated Aswaja Values in Shaping Religious Moderation at Primary School: Integrasi Nilai-Nilai Aswaja dalam Membentuk Moderasi Beragama di Sekolah Dasar - Isbah, Muhammad Faliqul; Hamzah, Ghufron; Martanti, Fitria (Indonesian Journal of Education Methods Development, 2026)
General Background Indonesia’s social and religious plurality requires Islamic education models that cultivate not only individual piety but also moderate and inclusive religious attitudes from the primary level. Specific Background Islamic primary education grounded in Ahlussunnah wal Jama’ah (Aswaja) values has been practiced at SD Islam Permatasari Mijen Semarang through an integrated educational approach aligned with the Merdeka Curriculum. Knowledge Gap Empirical studies examining how integrated Aswaja-based education operates at the primary school level and shapes students’ religious moderation remain limited. Aims This study aims to analyze the implementation of integrated religious education based on Aswaja values in strengthening religious moderation among primary school students. Results Using a qualitative case study design, the findings show that Aswaja values—tawassuth, tasamuh, tawazun, i‘tidal, and ta’awun—are internalized through classroom learning, religious habituation, and school culture. These practices foster tolerant, fair, non-exclusive, and socially responsive religious attitudes among students. Novelty The study demonstrates a structured model of integrated Aswaja-based education at the primary level that embeds religious moderation as lived practice rather than abstract doctrine. Implications The findings suggest that integrated Islamic education rooted in moderate religious traditions can serve as a foundational mechanism for character formation and social harmony within pluralistic societies. Highlights: Aswaja principles are internalized through the synergy of learning activities, habituation, and school culture. Students demonstrate tolerant and non-exclusive religious attitudes shaped by daily educational practices. Integrated religious education operates as a consistent character formation system at the primary level. Keywords: Aswaja Values, Religious Moderation, Integrated Education, Islamic Primary School, Character Formation